1999
DOI: 10.1093/acprof:oso/9780198296225.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Capitalism

Abstract: This book looks at how the shift to a knowledge-based economy is redefining firms, empowering individuals, and reshaping the links between learning and work using economic, management and knowledge-based theories, supported by empirical data, illustrations, and trends. The book argues that industrial-era models of firm-market boundaries, work arrangements, and ownership and control are inhibiting firms and individuals success in the emerging knowledge economy. New models are proposed based on knowledge-centred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…He showed that these account for the largest sectoral share of GDP and employment in the economy, and predicted that this share was destined to grow both absolutely and relatively over time. With brief interventions from Eliasson et al (1990) and Burton-Jones (1999) who further specified the knowledge intensity of sectors by value and labour qualifications respectively, on reach the statements of the Organization for Economic Cooperation andDevelopment (1996, 1999) calling for the measurement of the knowledge-intensity of national and regional economies (OECD/Eurostat, 1997).…”
Section: Konwledge-based-growth (Kgb) Theorymentioning
confidence: 99%
“…He showed that these account for the largest sectoral share of GDP and employment in the economy, and predicted that this share was destined to grow both absolutely and relatively over time. With brief interventions from Eliasson et al (1990) and Burton-Jones (1999) who further specified the knowledge intensity of sectors by value and labour qualifications respectively, on reach the statements of the Organization for Economic Cooperation andDevelopment (1996, 1999) calling for the measurement of the knowledge-intensity of national and regional economies (OECD/Eurostat, 1997).…”
Section: Konwledge-based-growth (Kgb) Theorymentioning
confidence: 99%
“…Among these scientists, the works of Boutang (2007), Burton (1999), Florida (2002), Fumagalli (2007), Gorz (2003), Murrau (2010), Procopio (1999), Rossiter (2006), Rullani (2004), and Vercellone (2007) should be noted. It is emphasized in this category that the modern period is identified as capitalism transformation, where the cognitive component acts as a destructive element of basics and principles of the capitalist mode of production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Neoliberalism in higher education has been a constant force for change over the past few decades all over the world. Privatization and commercialization, as well as the growth of capitalist and corporate influence over higher education institutions, characterize neoliberal policies in higher education (Barnett, 2000;Burton-Jones, 1999;Carnoy & Rhoten, 2002). As Barnett (2000, p. xxxi) wrote, "In the neoliberal model, higher education is ideally integrated into the system of production and accumulation in which knowledge is reduced to its economic functions and contributes to the realization of individual economic utilities.…”
Section: Introductionmentioning
confidence: 99%